Proposed Research priorities for Doctoral dissertations in educational administration at Taibah University and the Islamic University in Al-Madinah - Alyahyan, Maha Saleh Saad; Alsubhi, Wafiah Othman; Aljumah, Norah Mohamed (Journal of Educational and Psychological Sciences, 2025)
The Research aims to present a proposed vision for research priorities for doctoral dissertations in educational administration at some universities in the Kingdom of Saudi Arabia, namely Taibah University and the Islamic University in Al-Madinah. The research used a descriptive methodology utilizing a content analysis tool. The research yielded several key findings, including a focus on modern trends in educational leadership, measuring the efficiency of scientific research, and implementing governance in Saudi universities.